2016
DOI: 10.1111/1754-9485.12476
|View full text |Cite
|
Sign up to set email alerts
|

Volume changes with stereotactic body radiation therapy in early lung cancer: Time trends and outcomes

Abstract: Gross tumour volume undergoes significant changes during SBRT. Early regression in tumour volume may be used as a predictor of poor LRFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It concluded a correlation between a marked reduction in the size during the SBRT in early lung cancer and worse clinical outcomes, progression‐free survival and overall survival. 26 Repeated CBCT before and after each fraction has been proposed to address such a problem as a tool for the target volume monitoring in lung SBRT. 27 The addition of an automated method to delineate the target volume would help to figure out the magnitude of intrafraction and interfraction tumour deformations and the necessity to repeat the planning in case of undesired dosimetric violations, known as adaptive radiation therapy (ART).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It concluded a correlation between a marked reduction in the size during the SBRT in early lung cancer and worse clinical outcomes, progression‐free survival and overall survival. 26 Repeated CBCT before and after each fraction has been proposed to address such a problem as a tool for the target volume monitoring in lung SBRT. 27 The addition of an automated method to delineate the target volume would help to figure out the magnitude of intrafraction and interfraction tumour deformations and the necessity to repeat the planning in case of undesired dosimetric violations, known as adaptive radiation therapy (ART).…”
Section: Discussionmentioning
confidence: 99%
“…Another study retrospectively observed the interfraction tumour volume change in twenty‐two patients. It concluded a correlation between a marked reduction in the size during the SBRT in early lung cancer and worse clinical outcomes, progression‐free survival and overall survival 26 . Repeated CBCT before and after each fraction has been proposed to address such a problem as a tool for the target volume monitoring in lung SBRT 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathak et al [24], using KVCT obtained before each fractional treatment, analyzed the changes that might occur during SBRT in 22 lung cancer patients. Their results showed that total tumor volume changed significantly during SBRT.…”
Section: Disease Markersmentioning
confidence: 99%